THE ROLE OF MALAY LANGUAGE AND LITERATURE AS A MEDIA FOR PEACE IN PATANI THAILAND AND THE ARCHIPELAGO - Jehwae, Phaosan (Journal of Malay Islamic Studies, 2018)
The existence of Malay language and literature has a very strategic meaning in the region of Southeast Asia, not only in the aspect of communication and interaction among the Malays, but also the relations between Malays and non-Malays, between minorities and the majority. This paper attempts to explain that in fact the Malay language has become a means of communication and interaction that is able to foster peace in various countries in the Nusantara or Southeast Asia region. While in Southern Thailand, the Patani community is not easy to live peacefully because Malay is less understood by government officials working in Southern Thailand. It also explains that one of the keys to fostering peace in the region is to make Malay language grow naturally, it is not complicated to use it and is also used by some government apparatus working in the provinces with the majority of Malays.